PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA APARATUR SIPIL NEGARA BADAN KEPEGAWAIAN DAERAH KABUPATEN TOJO UNA-UNA - Ridwan, Ridwan (Katalogis, 2017)
The study intends to analyze the influence of leadership style and motivation on officialsâ€™ performance in the Agency of Regional Employment in Tojo Una-Una District. Type of research is descriptive analysis by wherein it describes the influence between variables, in this case, leadership style, motivation, and performance. Unit analysis is 40 officials who hold civil servants status. Analysis tool used is multiple linear regressions. The results show that leadership styleÂ and motivation influence the performance of officers in Tojo Una-Una District, both simultaneously and partially.